The Kumtag meteorite strewn field. Issue 12 (15th June 2021) - Du, Ke; Li, Shijie; Leya, Ingo; Smith, Thomas; Zhang, Dongliang; Wang, Peng
Abstract: The Kumtag meteorite strewn field was found in the Kumtag desert, 132 km south of Hami city in the Xinjiang province, China. It is an ellipse of 2.5 × 7.9 km, with a long axis extending along the northeast-southwest direction. The largest individual meteorite of the strewn field weighs about 10 kg; the smallest individual has a mass of only 27 g. In total, more than 100 individuals with a total mass of more than 180 kg were collected. The location and the distribution of the fragments suggest that the Kumtag meteoroid entered the atmosphere in the direction Northeast-Southwest. All meteorites collected in this strewn field are samples from the same unique meteorite shower. The Kumtag meteorite is an H5 ordinary chondrite with a shock stage S2, and a weathering grade W2. The cosmic ray exposure age of Kumtag is 6.7 ± 0.8 Ma, which is rather typical for H chondrites and which indicates that Kumtag was derived from the massive impact event on its parent body 7 Ma ago. A significant amount of He has been lost during certain unknown processe(s) before the Kumtag meteorite was ejected from its parent body.